Zhalim dalam Perspektif Al-Qur’an: Analisis Lafaz al-Ẓālimūn dalam Al-Tafsīr al-Munīr Karya Wahbah al-Zuḥailī dan Relevansinya dalam Konteks Indonesia - Rispan Efendi Lubis (Lembaga Yasin AlSys, 2026)
The concept of injustice (ẓulm) in the Al-Qur’an is often understood narrowly as limited to social injustice, whereas semantically and theologically it encompasses broader, multidimensional meanings. The scarcity of studies that specifically analyze the terms al-ẓālimūn and al-ẓālimīn in contemporary exegesis and their relevance to the Indonesian social context constitutes an important academic gap. This study aimed to analyze the meanings of al-ẓālimūn and al-ẓālimīn in the Al-Qur’an based on Wahbah al-Zuḥailī’s interpretation in Al-Tafsīr al-Munīr and to examine their relevance to the Indonesian social context. This qualitative, library-based research employed a thematic exegesis (tafsir tematik/maudhu‘i) approach. The primary data consisted of Qur’anic verses containing these terms along with their interpretation in Al-Tafsīr al-Munīr, while secondary data were drawn from exegetical literature and relevant scholarly journals. The analysis was conducted using a descriptive-analytical procedure through the stages of data reduction, thematic classification, interpretation, and contextualization. The findings show that, according to Wahbah al-Zuḥailī, injustice encompasses three main dimensions: theological injustice (shirk and disbelief), social injustice (rights violations and structural inequality), and moral–spiritual injustice (sin and betrayal of trust), indicating that injustice in the Qur’anic perspective is comprehensive and integrates theological, moral, and social dimensions. This concept carries important implications as an ethical foundation for responding to corruption, legal inequality, and moral crises in Indonesia, as well as serving as a normative framework for Qur’an-based social reform.